Evaluation of Antimalarial and Cytotoxic Activity of Styrylquinolines obtained from 8-Hydroxyquinaldine with Aromatic Aldehydes (2014)
This study reports the synthesis of five (E)-Styrylquinolines (Q.1, Q.2, Q.3, Q.5, Q.6) and three O-alkylated derivatives (Q.1a, Q.6a, Q 6 b) and the evaluation of its antimalarial activity and cytotoxic in vitro -- For Styrylquinolines Perkin condensation reaction type from 8-hydroxyquinaldine with aromatic aldehydes was used -- Antimalarial activity was performed using the method Radioisotope with FCB-2 strains of Plasmodium falciparum (chloroquine-resistant) and for the cytotoxic activity the MTT method with HepG2 cells was employed -- Most compounds showed to be active antimalarial -- Those with higher activity were Q.3 (IC506.4μM) and Q.5 (IC5010.8 µM), although all of them were cytotoxic at concentrations above 1 µg / mL -- The structures of these compounds were confirmed using infrared spectroscopy techniques and MRI in one and two dimensions